Docosahexaenoic acid increases accumulation of adipocyte triacylglycerol through up-regulation of lipogenic gene expression in pigs. Issue 1 (December 2017) - Huang, Chao-Wei; Chen, Yu-Jen; Yang, Jui-Ting; Chen, Ching-Yi; Ajuwon, Kolapo; Chen, Shuen-Ei; Su, Nan-Wei; Chen, Yu-Shan; Mersmann, Harry; Ding, Shih-Torng
Abstract Background Changing dietary fatty acid composition in modern diet influences the prevalence of obesity. Increasing evidences suggest favorable effects of n-3 PUFA for protecting against obesity and the metabolic syndrome. However, the regulation of n-3 PUFA in adipose is still unclear. Thus, this study addressed metabolism of different dietary fats in the adipose tissue of porcine model. Methods Eight-week-old cross-bred pigs were randomly assigned to three groups and fed a 2% fat diet for 30 days from either soybean oil (SBO), docosahexaenoic acid (DHA) or beef tallow. An in vitro experiment was conducted in which linoleic acid (LA), DHA or oleic acid (OA) were added to represent the major fatty acid in the SBO-, DHA- or BT- diets, respectively. Adipocytes size and lipid metabolism related genes were analyzed. Results Plasma triacylglycerol (TAG) was lower in DHA- than in BT-fed pigs, and the product of lipolysis, glycerol was highest in BT-fed pigs. In addition, expression of the lipolytic genes, adipose triglyceride lipase and hormone sensitive lipase was higher in BT-fed pigs and with OA treatment in vitro. DHA promoted protein kinase A activity in pigs without affecting lipolytic genes. Adipocyte cell sizes, TAG content and expression of lipogenic-related genes including, adipose differentiated related protein (ADRP) and diacylglycerol acyltransferase 1 (DGAT1) were elevated by DHA in vivo and in vitro, indicating DHA promoted adipogenesis to trap TAG in adipose tissue. Fatty acid β-oxidation genes were increased in the DHA-fed pigs. Conclusion This effect was partly explained by the effect of DHA to promote adipogenesis to trap TAG in adipocytes and also increase expression of genes involved in adipocyte fatty acid oxidation. Therefore, our results suggest a direct effect of DHA on adipocyte metabolism, resulting in TAG turnover and fatty acid dissipation to facilitate plasma lipid uptake from the circulation.